Immunomodulation in Endometrial Cancer. Issue 4 (1st April 2009) - Brooks, Nicole; Pouniotis, Dodie S.
Abstract : Endometrial cancer is the most frequent gynecological cancer and the fourth most common cancer in women in the developed world. Over the last decade, immunotherapy has been the focus of intense investigation as a form of cancer treatment whereby the treatment initiates a host immune response ultimately eradicating the tumor. It has been suggested that in endometrial cancer and many other forms of cancer, immunosuppression poses a significant obstacle at inducing antitumor immunity by immunotherapy. This review will look at the different studies that have identified immunomodulation of T cells, cytokines and macrophages, and regulation of apoptotic and angiogenic factors in endometrial cancer patients that may contribute to the inefficiency of immunotherapy.